Circular RNAs: emerging players in asthma and COPD - Liu, Xiaoying; Ali, Md Khadem; Dua, Kamal; Mao, Yuqiang; Liu, Jun (Frontiers in Cell and Developmental Biology, 2023)
Circular RNAs (circRNAs) belong to a unique class of endogenously expressed non-proteincoding RNAs with a distinct circularized structure, characterized by the absence of 5'-cap and 3'polyadenylate ends. They are generally formed through back-splicing from pre-mRNAs. They serve as regulators of transcription and splicing, and act as sponges for microRNAs (miRNAs) and RNA-binding proteins, thereby modulating the expression of target genes. As a result, they exert a substantial impact on a diverse array of cellular and biological processes, including cell proliferation, migration, inflammation, and oxidative stress. Asthma and COPD are chronic airway conditions that currently have no cure. In recent years, emerging evidence suggests that altered expression of circRNAs in airway, bronchial and immune cells is involved in asthma and COPD pathogenesis. Studies exploring circRNA dysregulation in asthma have showcased their involvement in regulating the proliferation, migration, and inflammation of airway smooth muscle and bronchial epithelial cells, as well as impacting goblet cell metaplasia, Th2 cell differentiation, and macrophage activation, primarily through interactions with miRNAs.Similarly, in COPD, circRNAs have shown altered expression patterns in the blood and lungs of patients, and these changes have been linked to modulating inflammation, oxidative stress, and airway remodeling in preclinical models. Furthermore, certain circRNAs have demonstrated promising potential as diagnostic and prognostic biomarkers for both asthma and COPD. This review delves into the current understanding of the function and molecular mechanisms of circRNAs in asthma and COPD, along with exploring their potential as biomarkers in these respiratory conditions.